Estudo fisiológico, sanitário e manejo de doenças em sementes florestais da Resex Quilombo do Frechal em Mirinzal/MA - Rosário, Wildinson Carvalho do (2020)
This work aimed to carry out the physiological, sanitary characterization and the management of fungal diseases of seeds of forest species of RESEX Quilombo do Frechal. RESEX has an area of 9,542 hectares, is located in the Baixada Ocidental Maranhense (2 ° 2 '00' 'S; 44 ° 48' 00 '' W) and covers an area of 9,542 hectares in the municipality of Mirinzal and is divided between the communities Frechal, Rumo and Deserto, with a population of approximately 900 people. The experiments were carried out at the Phytopathology Laboratory and in the Greenhouse, of the Agronomic Biotechnology Center of the State University of Maranhão - UEMA, Campi São Luís / MA. Seeds of four forest species, juçara (Euterpe oleraceae), genipap (Genipa americana), annatto (Bixa orellana) and calabash (Crescentia cujete), were collected manually, in the first half of 2019 at RESEX Quilombo do Frechal, municipality of Mirinzal / MA . The seeds went through the superficial disinfestation process with distilled water, 70% alcohol and 5% sodium hypochlorite before the experiments were carried out. In the physiological characterization, germination, emergence, water content, germination speed (IVG) and emergency (IVE) tests were performed. The health characterization was performed by the Blotter Test method and the identification of phytopathogens in the seeds was carried out according to dichotomous identification keys. In the alternative management, Bacillus isolate and neem oil were tested, being carried out through two independent experiments in a completely randomized design (DIC), with four treatments and eight repetitions. Experiment one was carried out by the microbiolization process of forest seeds with Bacillus methylotrophicus, multiplied in BDA culture medium and taken to the BOD for growth for 72 hours at 28 ° C and 12 hours photoperiod and in experiment two, the seeds were treated with neem oil 15% by spraying with the aid of a manual sprayer. Each treatment consisted of T1 juçara, T2 genipap, T3 annatto and T4 calabash. The witness consisted of the seeds immersed in distilled water. The seeds of juçara, genipap, annatto and calabash, obtained 9.0%, 67.00%, 17.50%, 63.5% of germination; 0.5%, 7.00%, 0.5%, 63.5% emergency; 22.81%, 12.15%, 15.66%, 8.73% water content respectively. The phytopathogenic fungi with the highest incidence were Penicillium sp., Aspergillus niger, Fusarium oxysporum, in the forest seeds of calabash, genipap, juçara and annatto, respectively. It was inferred that B. methylotrophicus and neem oil are promising alternatives to the control of phytopathogenic fungi.